Pathogenicity of porcine deltacoronavirus (PDCoV) strain NH and immunization of pregnant sows with an inactivated PDCoV vaccine protects 5‐day‐old neonatal piglets from virulent challenge - Zhang, Jialin (Transbound Emerg Dis, 2019)
In this study, the pathogenicity of porcine deltacoronavirus (PDCoV) strain NH (passage 10, P10) was evaluated. We found that PDCoV strain NH is enteropathogenic in 5‐day‐old pigs. Pathogenicity experiments provided a challenge model for studying the protection efficiency of passive immunity. In order to investigate the protective efficacy of passive immunity in newborn piglets, pregnant sows were vaccinated with either a PDCoV‐inactivated vaccine at the Houhai acupoint (n = 5) or DMEM as a negative control (n = 2) using a prime/boost strategy 20 and 40 days before delivery. PDCoV spike (S)‐specific IgG and neutralizing antibody (NA) responses were detected in immunized sows and piglets born to immunized sows. PDCoV spike (S)‐specific sIgA was also detected in the colostrum and milk of immunized sows. Five days post‐farrowing, piglets were orally challenged with PDCoV strain NH (10(5) TCID(50)/piglet). Severe diarrhoea, high levels of viral RNA copies and substantial intestinal villus atrophy were detected in piglets born to unimmunized sows. Only 4 of 31 piglets (12.9%) born to immunized sows in the challenge group displayed mild to moderate diarrhoea, lower viral RNA copies and minor intestinal villi damage compared to piglets born to unimmunized sows post‐challenge. Mock piglets exhibited no typical clinical symptoms. The challenge experiment results indicated that the inactivated PDCoV vaccine exhibited 87.1% protective efficacy in the piglets. These findings suggest that the inactivated PDCoV vaccine has the potential to be an effective vaccine, providing protection against virulent PDCoV.